The late Paleocene-Eocene interval of the Magallanes-Austral Basin (Chile-Argentina): Palynostratigraphy, paleoclimate and geochemical data - Quattrocchio, Mirta Elena (2023)
The Magallanes-Austral Foreland Basin preserves an important record of orogenesis and landscape evolution in the Patagonian Andes of Chile and Argentina. This paper evaluates the comparison between the thick Paleogene sequences in the Chilean Peninsula Brunswick (Chorrillo Chico and Agua Fresca formations) and the reduced Paleogene sequence (La Barca Formation) in the Punta Ainol locality, Argentina, by taking account of palynological and geochemical analyses. Warm and humid subtropical conditions (Subtropical Gondwanic Paleoflora) are inferred for the late Paleocene-Eocene interval studied. A new record of Lactoridaceae in the La Barca Formation expanded the known fossil range of this family in Patagonia. During the late Paleocene the Chorrillo Chico and La Barca formations would have been deposited mainly from hyperpycnal flows and this accumulation process continued until the Lutenian in the La Barca Formation. A relative rise in the sea level in the early Eocene would be recognized in both sections. In the middle Eocene a relative fall in the sea level would have occurred with increased terrigenous influx. The rate of sedimentation was similar in both sections during the Thanetian and Ypresian intervals according to the ages assigned by biostratigraphy, suggesting that the sedimentation rate would have been controlled mainly by relative changes in sea level during the Paleocene-Eocene transition. Paleoenvironmental changes during the Paleocene-Eocene transition were characterized at the La Barca Formation of the Punta Ainol section, considering the new geochemical and palynological data provided in this contribution.